(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Population growth is caused by birth rate, death rate and migration. Rapid enlargement in population is a major question in the developing world counting India as these economies have limited capital and therefore suffer from the problems of overpopulation via food shortage, poor health services, poor infrastructure, and environmental degradation and so on. If govt. of such economies makes expenses to boost one area e.g. agriculture and then industry suffers due to shortage of resources. This necessitates vital need for stabilizing population growth in such economies to get rid of the common troubles of population explosion. Against this back ground, this paper examines population characteristics based on growing population in Assam state of India which has been suffering from the problems of population explosion for long. Based on census data and by applying observational method for analyzing the objectives of the study, we find that the rate of growth of population in Assam. The study also focused on solidity of population and sex ratio in Assam during 1901-2011.While sex ratio has improved during the last three decades (1991-2011) although the number of females is still less than males in Assam.